1994
DOI: 10.1021/om00021a035
|View full text |Cite
|
Sign up to set email alerts
|

(.eta.3-Oxaallyl)rhodium(I) Complexes as Catalyst Precursors for the Disproportionation of Aldehydes

Abstract: Addition of 50 equiv of benzaldehyde to a benzene solution of (Ph3P)2Rh(?y3-CH2C(Ph)0) (1) resulted in rapid disproportionation of the aldehyde, yielding benzyl benzoate in near quantitative yield. Similar disproportionation reactions occurred with isobutyraldehyde, n-heptanal, and furfural; however, the yields in these reactions were lower. The catalytic efficiency of the (?73-oxaallyl)rhodium(I) complex depended on the -substitution pattern of the aldehyde, the concentration of the aldehyde, and the polarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…In part, the development of these synthetic methodologies has been facilitated by the previous understanding of the chemistry of this kind of compounds. Studies on late transition metal enolates have focused mainly on C−C bond-forming reactions, such as aldol-type condensations, , cross-coupling reactions with aryl halides, and, more recently, conjugated additions to α,β-unsaturated ketones . In general, it is widely admitted that precoordination of the electrophile to the metal center plays an important role in the reactivity of enolates, 1a,, enhancing their reactivity and stereoselectivity (Scheme ), but a precoordinative step is not a strict requisite for these reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In part, the development of these synthetic methodologies has been facilitated by the previous understanding of the chemistry of this kind of compounds. Studies on late transition metal enolates have focused mainly on C−C bond-forming reactions, such as aldol-type condensations, , cross-coupling reactions with aryl halides, and, more recently, conjugated additions to α,β-unsaturated ketones . In general, it is widely admitted that precoordination of the electrophile to the metal center plays an important role in the reactivity of enolates, 1a,, enhancing their reactivity and stereoselectivity (Scheme ), but a precoordinative step is not a strict requisite for these reactions.…”
mentioning
confidence: 99%
“…Studies on late transition metal enolates have focused mainly on C−C bond-forming reactions, such as aldol-type condensations, , cross-coupling reactions with aryl halides, and, more recently, conjugated additions to α,β-unsaturated ketones . In general, it is widely admitted that precoordination of the electrophile to the metal center plays an important role in the reactivity of enolates, 1a,, enhancing their reactivity and stereoselectivity (Scheme ), but a precoordinative step is not a strict requisite for these reactions. Our group has carried out several studies on O - bound metallacyclic enolate complexes of nickel of composition where the enolate functionality is rigidly held apart from the metal center .…”
mentioning
confidence: 99%
“…The use of a trialkyl phosphine ligand rather than a triaryl phosphine generally led to a higher yield of the product. It was reported that (π‐allyl)bis(triphenylphosphanyl)rhodium does not react with benzaldehyde at room temperature 10. However, owing to the strong σ‐donor character of trialkyl phosphines, π‐allyl bis(trialkylphosphanyl)rhodium complexes appear to be nucleophilic enough to react with benzaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…The analogous β‐methoxypropanal produced small amounts of the desired adduct but the major pathway remained decarbonylation (Table 1, entry 3) 14. To obtain a stronger chelating interaction, we next examined sulfide‐substituted aldehydes;15 the reaction of β‐methylsulfanyl aldehyde 3 with methyl acrylate at 40 °C produced the hydroacylation adduct in 36 % yield along with side product (27 %) that originates from a Tischenko‐type process (Table 1, entry 4) 16. When dichloroethane was used as solvent and the reaction temperature was raised to 60 °C, the amount of side product decreased to <3 % and the conversion into the desired adduct increased to 96 % (Table 1, entry 5).…”
Section: Evaluation Of Aldehydes and Catalysts In Hydroacylation Reacmentioning
confidence: 99%